EVALUATION OF THE OUTCOME OF THE ILIZAROV TECHNIQUE FOR THE TREATMENT OF TIBIAL BONE AND SOFT TISSUE INJURY - RAZZAQUE, MA; HAIDER, MI; REHMAN, MU; SHAFIQ, M; AHMAD, T; AHMED, B (Biological and Clinical Sciences Research Journal, 2023)
This study was designed to assess the outcome of the illizarov method for treating patients with dead bone segments or open fractures along with severe soft tissue injury. This retrospective study was conducted at Bakhtawar Ameen Trust Hospital, Multan, from September 2019 to September 2022. A total of 35 patients having non-union tibial fractures and dead bone segments were included in the study. These patients had tibia grade 3 open fractures and had undergone bone grafting and soft tissue closure. The defective bone segment was debrided, and radical resection was done. Illizarov technique was performed on all subjects. All patients reported good smooth tissue coverage and bone transport. The mean docking period of bone transport in all subjects was 3.87 ± 0.45 months. A leg length discrepancy of 1 cm occurred in 4 subjects. No subject complained of pain at follow-up. The Illizarov method is effective for the management of bone and soft tissue injuries.